Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1371/journal.pone.0219440
|View full text |Cite
|
Sign up to set email alerts
|

Optimal use of statistical methods to validate reference gene stability in longitudinal studies

Abstract: Multiple statistical approaches have been proposed to validate reference genes in qPCR assays. However, conflicting results from these statistical methods pose a major hurdle in the choice of the best reference genes. Recent studies have proposed the use of at least three different methods but there is no consensus on how to interpret conflicting results. Researchers resort to averaging the stability ranks assessed by different approaches or attributing a weighted rank to candidate genes. However, we report he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 33 publications
3
67
0
Order By: Relevance
“…NormFinder calculates the stability score (S) based on the inter- and intra-group variation. However, it has been reported that including genes with high overall variation can affect the stability ranking of all genes with this method (22). This algorithm can potentially be improved after identifying and removing genes with high overall variation.. Actb , Sdha and Pgk1 were the most stable RGs, presented stability values lower than 0.3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NormFinder calculates the stability score (S) based on the inter- and intra-group variation. However, it has been reported that including genes with high overall variation can affect the stability ranking of all genes with this method (22). This algorithm can potentially be improved after identifying and removing genes with high overall variation.. Actb , Sdha and Pgk1 were the most stable RGs, presented stability values lower than 0.3.…”
Section: Resultsmentioning
confidence: 99%
“…This makes the identification of the best RGs very unwieldy. Using the same statistical methods, new approaches have been proposed, such as the “Integrated approach” (22) that has shown to provide a more accurate estimate of RG stability. It is advisable to devise integrated approaches based on suitability for each experimental setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest popularity acquired the "ready-to-use" user-friendly applets geNorm, NormFinder, and BestKeeper [19][20][21]. In spite of their drawbacks and occasional inconsistency in results, when compared side by side [15,27], these applets represent straightforward and valuable tools for routine RG testing. The source of the abovementioned inconsistency between the results of the applets lies in their unique algorithms assuming relative stability of the tested gene expressions.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, we are not aware of a serious survey and validation of stably expressed RGs in the rat spinal cord across postnatal development or after SCI. The issue was partially addressed by the study of Sundaram et al [15], who focused on the appropriate use of methods validating RGs' stability in the murine spinal cord. Several other papers deal with the validation of stable RGs in the spinal cord by neuropatic pain after spared nerve injury (SNI) and peripheral nerve injury (PNI) or after inflammatory injury [16][17][18].…”
Section: Introductionmentioning
confidence: 99%